Emergence of Regional Development Agenda in Nepal An Essay in Honour of Dr. Harka Gurung - Dahal, Kedar (Himalayan Review, 2009)
Not Available The Himalayan Review Vol. XXXVIII, 2007 (Harka Gurung Memorial Issue) Page: 101-117